Dependency and development in the garment industry: Commonwealth of the Northern Mariana Islands - Heidebrecht, Sarah E. (Kansas State University, 2011)
This study examines colonization, development, and globalization in the Commonwealth of the Northern Mariana Islands (CNMI) with respect to the garment industry, the main industry of the islands. A broad-reaching analysis examined population, gender, economic factors, and import/export data in order to explore the repercussions of garment industry development and subsequent decline on the CNMI. A quantitative analysis was conducted utilizing data from the United States Census Bureau, the CNMI's Department of Commerce, and the U.S. Department of Commerce Office of Textiles and Apparel. This research illustrates how the effects of the garment industry in small developing nations are dramatically impacted by a trade arrangement, the Multi-Fiber Arrangement (MFA), which was a protectionist measure used to restrict manufacturing of certain product through a quota system. In addition, this study reveals the economic implications and societal outcomes for the CNMI after the collapse of the garment industry as a result of the 2005 MFA phase-out. Garment production orders shifted to large producer nations once quota restrictions were no longer in place. Factory closures, lost business revenue, and a loss of manufacturing positions affecting predominantly women plagued the CNMI as well as cost-of-living increases. Federalization of the CNMI took place in 2009 which further complicated the islands’ politics and guest worker population status. Tourism is now the CNMI's chief industry although its growth is dismal and heavily reliant upon world economies. A comparison between Mauritius, another small island nation, concludes the discussion with insight on women's development and future considerations for economic growth as a means of development and dependency in the CNMI.
Keywords: Commonwealth of the Northern Mariana Islands; Apparel Industry; Multi-Fiber Arrangement; Garment Production; Women's Development; Economics, Labor (0510); Pacific Rim Studies (0561); Women's Studies (0453)